Pressure‐Controlled Structural Symmetry Transition in Layered InSe. Issue 6 (2nd May 2019) - Su, Huimin; Liu, Xuan; Wei, Chengrong; Li, Junning; Sun, Zeyuan; Liu, Qiye; Zhou, Xuefeng; Deng, Junhong; Yi, Huan; Hao, Qiaoyan; Zhao, Yusheng; Wang, Shanmin; et al.
Abstract: Structural symmetry of crystals plays important roles regarding the physical properties of two‐dimensional (2D) materials, particularly in the nonlinear optics regime. There has been a long‐term exploration of the physical properties in 2D materials with various stacking structures, which correspond to different structural symmetries. Usually, the manipulation of rotational alignment between layers in 2D heterostructures is realized at the synthetic stage through artificial stacking like assembling building blocks. However, the reconfigurable control of translational symmetry of crystalline structure is still challenging. High pressure, as a powerful external control knob, provides a very promising route to circumvent this constraint. Here, a pressure‐controlled symmetry transition in layered InSe is experimentally demonstrated. The continuous and reversible evolution of structural symmetries can be in situ monitored by using polarization‐resolved second‐harmonic‐generation (SHG) spectroscopy. As pressure changes, the reconfigurable symmetry transition of the SHG pattern from threefold rotational symmetry to mirror symmetry is experimentally observed in layered InSe samples and successfully explained by the proposed interlayer‐translation model. This opens new routes toward potential applications of manipulating crystal symmetry of 2D materials. Abstract : Structural symmetry of crystals plays important roles regarding the physical properties of 2D materials. A pressure‐controlled symmetry transition in layered InSe is experimentally demonstrated. The continuous and reversible evolution of structural symmetries can be in situ monitored by using polarization‐resolved second‐harmonic‐generation spectroscopy. This opens new routes toward potential applications of manipulating crystal symmetry of 2D materials .